Analysis of brand love on English football teams - Rahida Abd Rahman; Azleen Ilias (IDEAS, 2024)
This study aims to see the emergence of brand love for English Premier League (EPL) football teams. It was conducted on EPL football fans in Malaysia. The data was collected using an online questionnaire sent via social media to reach 150 respondents. Brand love is a construct composed of six dimensions: emotional attachment, high quality, brand connection, intrinsic rewards, thinking, and passion. The results indicated that the consequences of brand love for football teams are loyalty, word-of-mouth, and willingness to invest time.